Transformational leadership and career development on employee performance and job satisfaction as intervening variables - Nicholas Ananta Nst; Siti Mujiatun (Institute of Computer Science (IOCS), 2024)
This research aims to examine the role of transformational leadership sand career development on employee performance which is mediated by employee job satisfaction at PT. Alfa Scorpii Marelan. Design/methodology/approach: Data was collected from 47 workers working in the automotive industry, namely PT. Alfa Scorpii Marelan branch, Medan city. Data collection was carried out through a survey design. Data analysis was carried out through structural equation modeling using PLS-Smart. Findings: Transformational leadership was found to influence job satisfaction, career development influenced job satisfaction, transformational leadership influenced employee performance, career development influenced employee performance, job satisfaction influenced employee performance, job satisfaction did not mediate the influence of transformational leadership on employee performance, job satisfaction. mediating the influence of career development on employee performance at PT. Alfa Scorpii Medan Marelan. Originality/value : This study describes the mechanism of the relationship between servant leadership, job satisfaction and career development